STRATEGI PEMBELAJARAN DIAGNOSIS DALAM INTERNALISASI KURIKULUM BERBASIS CINTA DI MADRASAH ALIYAH AL-ITTIFAQI’AH - Muvtia Agustina; Ahmad Zainuri; Muslim Gani Yasir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze and describe diagnostic learning strategies in the internalization process of a love-based curriculum at Madrasah Aliyah Al-Ittifaqiah. A love-based curriculum is understood as an educational approach that emphasizes compassion, empathy, responsibility, and spirituality as the foundation for students’ character development. The primary challenge in its implementation lies in ensuring that values are not confined to cognitive understanding but are manifested in students’ attitudes and behaviors.This research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the principal and teachers, and analysis of instructional documents. Data analysis was conducted through systematic data reduction, display, and conclusion drawing. The findings reveal that diagnostic learning strategies were implemented through initial mapping of students’ characteristics, identification of learning needs and socio-religious backgrounds, and continuous formative assessment. Teachers utilized diagnostic results to design contextual, reflective, and exemplary-based learning processes.The study concludes that diagnostic learning plays a significant role in strengthening the internalization of love-based values through habituation, educational dialogue, and integration of values into classroom activities. It recommends enhancing teachers’ competencies in diagnostic assessment and developing structured character evaluation instruments to support the sustainability of love-based curriculum implementation in madrasah education.